Teaching methods of creating scientific style texts for master students - Dgebuadze, Marine ("Intercultural Dialogues" Transactions, 2023)
Academic writing is an obligatory discipline of study in master's and doctoral studies. The assimilation of this subject should develop the student's skills to create analytical and scientific texts. Therefore, studying academic writing is part of the study of rules of the scientific community. These rules are learned step by step, by writing texts and discussing them with different readers, giving and receiving feedback. Academic writing requires a review of previously done research. When searching for existing articles based on existing research, students should understand the methods of finding scientific works and be able to critically evaluate sources of information. The subject of the study and discipline largely determine which sources students should use in their work. The aim of teaching academic writing at the master's or doctoral level is to achieve a high quality of research papers submitted for the defense of the degree. The main task of the programs is also the development of research skills in students, teaching them to search for the information they need, such as: a) Viewing new literature on the subject (limiting the search to novelties) or visiting the library and locating the theme of interest in the catalogue; b) Performing a search for information related to the subject in the databases of libraries; c) Selection of interesting sources of information from references in the research literature that were found in databases; d) Acquaintance with the style of citation adopted in a particular program. The Ilia State University used two teaching methods for master and PHD Students: Project method and Peer review method. The proposed article details the results of a study that compares the two teaching methods, their effectiveness and preference, as well as a comparison of the quality of written papers submitted for defense of the degree, after the training phase of both methods.